Recovery of Behavioral Changes and Compromised White Matter in C57BL/6 Mice Exposed to Cuprizone: Effects of Antipsychotic Drugs - Xu, Haiyun; Yang, Hong-Ju; Rose, Gregory M.; Li, Xin-Min (Frontiers in Behavioral Neuroscience, 2011)
Recent animal and human studies have suggested that the cuprizone (CPZ, a copper chelator)-feeding C57BL/6 mouse may be used as an animal model of schizophrenia. The goals of this study were to see the recovery processes of CPZ-induced behavioral changes and damaged white matter and to examine possible effects of antipsychotic drugs on the recovery processes. Mice were fed a CPZ-containing diet for five weeks then returned to normal food for three weeks, during which period mice were treated with different antipsychotic drugs. Various behaviors were measured at the end of CPZ-feeding phase as well as on the 14th and 21st days after CPZ-withdrawal. The damage to and recovery status of white matter in the brains of mice were examined. Dietary CPZ resulted in white matter damage and behavioral abnormalities in the elevated plus-maze, social interaction and Y-maze test. Elevated plus-maze performance recovered to normal range within two weeks after CPZ withdrawal. But, alterations in social interaction showed no recovery. Antipsychotics did not alter animals’ behavior in either of these tests during the recovery period. Altered performance in the Y-maze showed some recovery in the vehicle group; atypical antipsychotics, but not haloperidol, significantly promoted this recovery process. The recovery of damaged white matter was incomplete during the recovery period. None of the drugs significantly promoted the recovery of damaged white matter. These results suggest that CPZ-induced white matter damage and social interaction deficit may be resistant to the antipsychotic treatment employed in this study. They are in good accordance with the clinical observations that positive symptoms in schizophrenic patients respond well to antipsychotic drugs while social dysfunction is usually intractable.